The Efektivitas Metode Peter Half Slope dalam Menentukan Kedalaman Benda Anomali - Syamsurijal Rasimeng; Ivana Jayarani; Maria Nova NafTalita; Tiara Andika Fadila; Ilham Dani; Rustadi (Jurnal Rekayasa Geofisika Indonesia, 2023)
The Peter Half Slope method is one of several techniques that can be used as the earliest quantitative depth determination. It is hoped that through this research the literature on the Peter Half Slope method can increase. This research aim is to prove the effectiveness of the Peter Half Slope method in estimating the depth of subsurface anomalous objects through comparison of models (synthesis) that have not and have been added random values as error values. This research begins with modeling in Geomodel software. After obtaining the appropriate synthetic modeling results, the next step is to perform processing in Matlab software to test the effectiveness of the Peter Half Slope method. After entering all the values, the average value of the anomalous depth of model 1 in d1, d2, and d3 is 100.1890m. As for model 2, the average value of model 2 anomaly depth is 97.35344m. The error between the original modeling and the modeling added random values using the Peter Half Slope method is 2.83%. Thus, this method is considered effective in determining the depth of subsurface anomalies through magnetic response, but to determine the exact depth requires the use of other methods as the main method.